English as a Medium of Instruction: Students’ Discernment in Nepal - Ghimire, Nani Babu (Education and Development, 2019)
English as a medium of instruction (EMI) has become a global phenomenon; and several countries of the world have adopted EMI in their classrooms from primary to university level including Nepal. This study seeks to explore the perception, practice and challenges of the students allied to using EMI for learning at secondary level in the community schools of Nepal. It looks at students’ attitude on EMI in terms of their upbeat mind-set, complicatedness and identity construction. A critical qualitative case study method was adopted for research and three students of an EMI-adopted community school of Sindhuli district were selected as the participants of study following the purposive sampling procedure. Semi-structured interview was conducted to elicit in-depth data from the participants. The raw data were transcribed and coded to develop the main themes maintaining the principles of relevancy. The findings reveal that the students have deeply rooted beliefs in learning through English because it secures their future by assisting them to get a job in the country or abroad. They have difficulties in speaking English and learning new vocabulary even though they are learning through English; but their teachers facilitate them with the Nepali equivalents. They feel proud of being the students of EMI schools because there is a superior credit of their school in the district and they are also supposed to be better qualified students in their locality.